Measuring of the effects of a sea turtle conservation education program on children's knowledge and attitudes in Grenada, West Indies. (1st October 2021) - Frame, Joseph R.; Good, Brandon; Slinger, Peter; Smith, Maia P.; Butler, Brian; Marancik, David
Abstract: Grenada, a multi-island country in the Caribbean Sea, supports aggregates of critically endangered hawksbill turtles ( Eretmochelys imbricata ), endangered green turtles ( Chelonia mydas ) and vulnerable leatherback turtles ( Dermochelys coriacea ). These species play an integral role within the marine ecosystem and are important to ecotourism in Grenada. They are also negatively impacted by anthropogenic factors in Grenada such as legal and illegal hunting, habitat loss, pollution, and by-catch. Conservation educational programs represent a powerful approach for increasing public knowledge about sea turtles and engaging stakeholders to improve management of sea turtle populations. However, little data is available that quantifies the impact that these programs have on participants. A 10 day, active-learning sea turtle education program was developed for 22, nine to twelve-year old children who were selected for participation by their school principles, on the island of Carriacou, a dependency of Grenada. Knowledge and attitude changes towards sea turtle biology and conservation were quantified with pre- and post-curriculum test scores consisting of multiple-choice basic biology questions (n = 15) and Likert-scale questions (n = 16) that assessed the variables understanding and concern, locus of control, and level of verbal commitment. Student's knowledge of sea turtle biology significantly increased 12.3 percentage points, including a 16.3 percentage point increase for females (n = 11) and 7.9 for males (n = 11). Likert-scale scores demonstrated that students held and maintained a positive attitude towards sea turtle conservation. Score changes were not significant but females trended towards a more positive attitude change for each variable post-curriculum while males trended towards less positive attitudes. Possible influences driving these gender differences are discussed. Public education remains central to engaging communities in sea turtle conservation and ocean resource management efforts in the Caribbean region. Understanding the effects of conservation education programs on participant knowledge and attitudes is central to our ability to progress the curriculum and better engage communities in conservation efforts. Graphical abstract: Image 1 Highlights: Human activity significantly impacts sea turtles in Grenada. A sea turtle conservation education program was developed for school children. Student's knowledge of sea turtles significantly increased with a greater score increase for females than males. Attitudes towards sea turtles remained positive while females trended more positive and males more negative. Gender influences may need to be addressed when developing turtle education programs in Grenada.